Durability of Polymer Concretes - Slopkova, Katarina (Communications - Scientific letters of the University of Zilina, 2002)
Decrease of the compressive strength and the flexural strength of polymer concretes based on an epoxy resin as a result of repetitive effect of frost, increased temperatures 40 °C and 80 °C and long-term water effect.